Confidential inquiry sheet and Voucher
1902-01-04 1902 1900s 3 pages GREAT NORTHERN CENTRAL HOSPITAL. CONFIDENTIAL INQUIRY SHEET. Name Age S. M. W. Address Children, or other Dependents Wages________________ If out of work, and how long_________________ Amount from Club_______________________________Extra, from gratuities Earnings of Wife, or Children Rents from Lodgers How long ill_________________________________________ Whether incapacitated by illness__________ If under previous treatment__________________________ Private or Hospital Doctor's Name Address Whether Member of Provident Dispensary , or Club Name of Club and Doctor Rent of Dwelling House or Lodgings Other information Date of Inquiry 189 378/IMSW/A/1/6/9a